2020
DOI: 10.1007/s11934-020-00993-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Urology Residency Applications: What Matters Most and What Comes Next?

Abstract: Purpose of Review In light of the announcement that the United States Medical Licensing Examination Step 1 exam will transition to pass/fail reporting, we reviewed recent literature on evaluating residency applicants with a focus on identifying objective measurements of applicant potential. Recent Findings References from attending urologists, Step 1 scores, overall academic performance, and research publications are among the most important criteria used to assess applicants. There has been a substantial incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 46 publications
(86 reference statements)
0
25
0
Order By: Relevance
“…Program directors have rated interaction with residents or faculty as the perceived objective of visiting sub-internships. 2 , 7 , 8 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Program directors have rated interaction with residents or faculty as the perceived objective of visiting sub-internships. 2 , 7 , 8 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…Another potential influence of home match rates may be the differing number of IMGs and non-senior medical graduates who historically are more likely to match in neurosurgery and urology as compared to plastic surgery and otolaryngology. Analysis of NRMP and American Urological Association match data (the urology match does not participate in NRMP) found that neurosurgery programs matched a significantly higher number of IMGs (p < 0.001), while urology residencies matched a significantly higher number of non-seniors (p < 0.001; Table 3 ), compared to plastic surgery and otolaryngology 12 , 13 This discrepancy underscored an important and prevalent pathway likely through dedicated research for IMGs and non-seniors to have a successful match in neurosurgery and urology 2 , 20 Not surprisingly, these non-traditional applicants may have had exposure to programs at which they matched, emphasizing the notion that applicant familiarity (other than through traditional clinical away rotations) may still be held in high regard. We suspect that the high number of IMGs and non-senior medical graduates among neurosurgery and urology residencies may have washed out the home matching effect as seen in plastic surgery and otolaryngology during the 2020 to 21 application cycle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the trend of increased application numbers for individual specialties has been published [8][9][10][11][12][13][14][15][16], the comparison between applications, interview invites, and interviews attended across the spectrum of virtual and in-person interviews has not been examined.…”
Section: Introductionmentioning
confidence: 99%